A new species of Cacatuocotyle (Monogenea, Dactylogyridae) parasitizing Astyanax spp. (Characiformes, Characidae) from Brazil, including molecular data and a key to species identification - Zago, Aline Cristina [UNESP]; Franceschini, Lidiane [UNESP]; Müller, Maria Isabel [UNESP]; Silva, Reinaldo José Da [UNESP] (Springer Nature, 2018)
The present study describes Cacatuocotyle papilionis n. sp. (Monogenea, Dactylogyridae) from the skin of the characid fishes Astyanax lacustris (Lütken, 1875) (=Astyanax altiparanae Garutti & Britski, 2000) and Astyanax fasciatus (Cuvier, 1819) (Characiformes, Characidae) from the Southeast of Brazil, supported by morphological and molecular data. The new species differs from all congeners, mainly due to the morphology of the ventral bar (resembling a butterfly), accessory piece, and the number of rings of the male copulatory organ (MCO), comprising a coiled tube with 4.5-5.5 counterclockwise rings. The first molecular data for this monogenean genus is provided in this study, using the partial sequences of the ribosomal gene (28S), as well as providing an identification key to the species.
Keywords: 28S rDNA fragments; Characid fishes; ectoparasite; monogenean; Neotropical region